LGBTQ Older Adults in Long-Term Care Settings: An Integrative Review to Inform Best Practices. Issue 5 (20th October 2022) - Fasullo, Katherine; McIntosh, Erik; Buchholz, Susan W.; Ruppar, Todd; Ailey, Sarah
ABSTRACT: Objectives: To synthesize literature about lesbian, gay, bisexual, transgender, and queer (LGBTQ) older adults in long-term care (LTC) facilities and provide recommendations for best practice guideline development to inform practice, research, and policy. Methods: Four electronic databases were searched in June 2019 for studies conducted between 2000– 2019 related to caring for LGBTQ older adults in LTC settings. An integrative literature review was conducted on the twenty eligible studies. Results: LGBTQ participants fear discrimination in LTC settings leading to the invisibility of their identities. They recognize a need for increased staff training and the importance of community networks and facility preferences. LTC staff have mixed experiences with inclusive practices and complex views of LGBTQ older adults. LTC staff experience training deficits and require more expansive modalities. Conclusions: LGBTQ participants and LTC staff both advise that LTC facilities revise forms and policies to ensure all sexual orientations and gender identities are affirmed and protected in addition to providing widespread training. Clinical Implications: This review calls to attention the need for LTC settings to uniformly follow best-practices. Clinical recommendations to promote equitable healthcare include: staff training at all levels and communication that does not assume heterosexuality or cisgender identity.